TMSOTf-Promoted Addition of Alkynes to Aldehydes: A Novel Synthesis of Chroman-4-ones - Park, Ji Yeon; Ullapu, Punna Reddy; Choo, Hyunah; Lee, Jae Kyun; Min, Sun-Joon; Pae, Ae Nim; Kim, Youseung; Baek, Du-Jong; Cho, Yong Seo (WILEY-V C H VERLAG GMBH, 2008)
A novel synthetic method to prepare chalcones 2 and chroman-4-ones 3 by TMSOTf-promoted addition of alkynes 1 to various aldehydes has been developed. The ratios of chalcones 2, chroman-4-ones 3 and hydrated products 4 varied depending upon the substituents R (nBu, phenyl, H and TMS) on the alkynes 1. We also describe the transformation of the chalcones 2 to the corresponding chroman-4-ones 3 under basic conditions. ( (C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: COUPLING REACTION; ASYMMETRIC-SYNTHESIS; FLAVANONES; HYDRATION; CHROMANONES; ACID